Caracterización físico- química de la biomasa residual del cultivo de cacao (Theobroma Cacao L), naranja (Citrus Sinensis, Variedad Valenciana,) y mandarina (Citrus Reticulata) en la provincia Bolívar - Castro Ycaza, Katherine Valeria (2015)
In the city Guaranda, Sector Laguacoto 1, Bolivar University State of, School of Agro industrial Engineering Counterfoil carried out the investigation that took as an aim the quantification of the residual agricultural Biomass in the province Bolivar, the applied design was a design completely at random with three repetitions, the above mentioned test allowed to evaluate the quantity of biomass calculated of the crops of cocoa, orange and mandarin in the cantons Caluma and Las Naves and to identify what mathematical model takes refuge of better way for every type of crop. On Having realized the Recognition of the studied Places A perspective was carried out as for the area of study, his magnitude and significance, this Information took so much of the Canton Las Naves as of the Canton Caluma taking 50 as an area of study x 50 meters in which 10 trees were chosen completely at random and of each of these they were pruned 10ramas. They were taken measurements of the variables dendométricas of total height, height of the trunk, height of the glass, diameter of the trunk and diameter of the glass, for the calculation of Biomass, which took as results that in the Canton Caluma exists brought near of 1 ' 226.080 Kg in the crop of cocoa, in that of orange were obtained 4'199.979 Kg, and finally in the crop of mandarin 34.036 kg. On the other hand in the Canton Las Naves were obtained 2'557.670 Kg in the crop of Cocoa, in that of orange 1 ' 518.541 Kg and in that of mandarin 64.727 kg. Once located the samples in the surface of dried (cement), were taking small portions of the same ones to be analyzed and to determine his percentage of dampness activity that was realized every day until this one becomes stable, reaching a constant value of 11 % in 24 days. Finally it carried out the elemental analysis process in which the percentage of carbon, hydrogen and nitrogen in the above cultures was determined